Integrated Value in the Consumer Products and Services Industry : Determinants, Measurement, and Implications - Bujdošová, Alžbeta; Procházka, David, 1979 říjen 10.-; Petera, Petr, 1976-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2026)
This master thesis explores the integrated value model as a valuation model and a tool for managerial decision making in area of ESG improvement. The aim is to identify the correct valuation after internalisation of social and environmental externalities and its comparison to market value on a sample of twenty-nine companies within the selected industry from STOXX Europe 600 ESG-X index. Calculation of the integrated value consisted of three phases – calculation of financial value according to DCF model and calculation of social and environmental value, which was bound to quantification and monetization of the yet unmonetized effect of company on society and environment. The assumption of partial integration of externalities in market value was applied resulting from existence of active investors in market and application of various studies suggesting the partial correlation between improved responsibility profile of the company on its financial value. In conclusion, the empirical evidence revealed no significant integration of selected environmental and social impact of the firm´s activities in company´s market value as there was no significant difference identified between calculated financial value and market value. However, for two companies, the integration can be partially identified due to otherwise overrated terminal value growth.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses